Effect of different type of car to tire deformation - Hong, Kim Soon (2008)
Tire is one of the important part in car which it play an important role in automotive industry. In recent years, much progress has been made in the physical understanding to measure the value deformation of the tire. The objective of this project is to study the effect of the different type of car to tire deformation using FEA software. The structural model of the tire was developed using the computer aided design software SOLIDWORKS. Finite element modeling and analysis was performed utilizing the ALGOR software with one condition that is at normal road. It can be seen that from the result, tire deformation increases when the speed and weight of car increase. Three type of car have been selected in this project that is kancil, proton saga, and Toyota vois. The result of this project is the value of stress von mises and nodal displacement will increase when the tire spins more faster and when the weight of car increase.